PENGARUH BERBAGAI PERBANDINGAN PUPUK ORGANIK LIMBAH KULIT KAKAO (Theobroma cacao. L) TERHADAP PERTUMBUHAN SEMAI JATI (Tectona grandis L. f) - Megawati, Megawati; Muslimin, Muslimin; Umar, Husain (Universitas Tadulako, 2015)
An experiment to evaluate the effect of cacao pods waste as bioactive compost on growth of jati (Tectona grandis L f) seedlings . The research was conducted in greenhouse and laboratory forestry faculty Tadulako University, from February until April 2014. This study used experimental method by Completely Randomized Design (CRD) with four treatmeants.i.e: M0 (control), M1 (soil+compost cacao pods 1:1), M2 (soil+compost cacao pods 1:3) and M3 (soil+compost cacao pods 1:3). Each treatments was replicated six times, so there were 24 unit. The result of the experiment showed that the cacao pods compost significantly affect plant high, leaves count , and roots length but not significant effect on stem diameter. In addition the results of the study also showed that the control gave the best growth of jati seedlings comparing the other. This might be caused by the compost still decomposition processing. Key words: Compost Cacao Pods, Growth Jati Seedlings, Decomposition